Exploiting agent mobility for large-scale network monitoring. - Liotta, A.
As networks become pervasive, the importance of efficient information gathering for purposes such as monitoring, fault diagnosis, and performance evaluation increases. Distributed monitoring systems based on either management protocols such as SNMP or distributed object technologies such as CORBA can cope with scalability problems only to a limited extent. They are not well suited to systems that are both very large and highly dynamic because the monitoring logic, although possibly distributed, is statically predefined at design time. This article presents an active distributed monitoring system based on mobile agents. Agents act as area monitors not bound to any particular network node that can "sense" the network, estimate better locations, and migrate in order to pursue location optimality. Simulations demonstrate the capability of this approach to cope with large-scale systems and changing network conditions
Keywords: CORBA; Common Object Request Broker Architecture; SNMP; Simple Network Management Protoco; Active distributed monitoring system; Agent mobility; Distributed object technologies; Fault diagnosis; Large-scale network monitoring; Location optimality; Management protocols; Monitoring logic; Network management; Network node; Performance evaluation; Scalability problems; Simulations; Telecommunications management networks